2009
DOI: 10.1097/adm.0b013e31818fcc2c
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Source and Type of Alcohol Consumed by High School Students

Abstract: : These findings emphasize that when implementing evidence-based strategies to prevent underage drinking, such as enforcement of underage drinking laws and increasing alcohol excise taxes, attention should be paid to the source of and the usual type of alcohol consumed, and how these vary by drinking pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 11 publications
4
17
1
Order By: Relevance
“…Beer and wine were the most frequently endorsed beverage type for first sip(s) of alcohol. This stands in contrast to literature that indicates that distilled spirits are the most frequently consumed type of alcohol by adolescents, at least among high-schoolers (Cremeens et al, 2009;Siegel et al, 2011), but is consistent with Donovan and Molina (2008), who also found wine to be the most commonly endorsed beverage type for sipping/tasting. Distilled spirits may not appeal or are not available to children and preadolescents.…”
Section: Discussioncontrasting
confidence: 54%
“…Beer and wine were the most frequently endorsed beverage type for first sip(s) of alcohol. This stands in contrast to literature that indicates that distilled spirits are the most frequently consumed type of alcohol by adolescents, at least among high-schoolers (Cremeens et al, 2009;Siegel et al, 2011), but is consistent with Donovan and Molina (2008), who also found wine to be the most commonly endorsed beverage type for sipping/tasting. Distilled spirits may not appeal or are not available to children and preadolescents.…”
Section: Discussioncontrasting
confidence: 54%
“…Research on the types of alcohol beverages consumed by youth has implications for guiding regulatory and environmental strategies to reduce underage drinking (Cremeens et al, 2009). For example, governmental regulation, which is often alcoholic beverage-specific (e.g., advertising guidelines, alcohol excise taxes), has been shown to reduce underage drinking (Carpenter et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the 2011 Monitoring the Future (MTF) survey indicated that the prevalence of being drunk in the past month was similar for 8 th grade females and males (4.2% and 4.4%, respectively), but remained higher among 12 th grade males compared to females (28% versus 22%; Johnston et al, 2012). Findings regarding beverage-specific alcohol use by youth, particularly in the understudied group of adolescent females, could inform regulatory policy (e.g., beverage-specific advertising regulations) and alcohol prevention and intervention (Cremeens et al, 2009; Naimi et al, 2007; Roeber et al, 2007; Cremeens et al, 2009; Werch et al, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Our list of drinking-related terms used to acquire Tweets did not include all of the terms that are synonymous with drinking; hence, some drinking-related Tweets were missed. "Wine," although a popular alcohol term on Twitter (>500,000 Tweets per month), was not included in the fi nal term list because young people tend to prefer beer or distilled spirits over wine, and we presumed that wine-related Tweets could be qualitatively different from all the other alcohol-related Tweets in our study (Cremeens et al, 2009;Siegel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%